Hip Resurfacing Arthroplasty or Total Hip Arthroplasty? - Musbahi,O; Logishetty,K; Cobb,JP (2021)
Hip resurfacing arthroplasty (HRA) is an alternative to total hip arthroplasty (THA) in younger patients with good bone quality who wish to return to high levels of activity. Usage of HRA has declined due to implant-specific complications—metal debris and periarticular soft tissue damage, implant loosening, and femoral neck fracture. These were most common with implants which have now been withdrawn, but fears remain. HRA is more technically challenging than THA, but revision rates for patients operated at specialist centres are equivalent. Gait and biomechanical studies suggest that HRA better restores normal function compared to THA, and registry-based studies suggest a lower mortality. However, randomised clinical trials have not shown superiority using conventional patient-reported outcome measures. As the clinical indications are dependent on patient demands, and more active patients are more likely to wear out artificial joints, it is difficult to robustly compare HRA and THA. Today, safe HRA implants inserted by experienced surgeons in active, male patients seem to deliver the most predictable outcomes, high performance and longevity.